ASSESSMENT OF RENAL FUNCTION IN MALARIA PATIENTS IN MINNA, NORTH CENTRAL NIGERIA - Ogbadoyi, Emmanuel O.; Gabi, Baba (African Journal of Infectious Diseases (AJID), 2007)
Establishment of prevalence of malaria-associated renal impairment in Nigeria is important for proper prognosis and management of malaria and its associated complications. Using biuret method for protein estimation, alkaline picrate-slot method for creatinine and urea estimation, and flame photometry and titrimetric method for electrolytes estimation, selected kidney function parameters which included proteinuria, serum levels of urea, creatinine and electrolytes were determined in 169 malaria patients and in 58 individuals without malaria. Data obtained were analyzed using one-way analysis of variance to compare variation among malaria patients and individuals without malaria, Duncan multiple range test to compare variation among means, and correlation matrix to evaluate correlation between the parameters measured. Proteinuria in malaria cases differed significantly (p< 0.05) from individuals without malaria, and a positive correlation existed between proteinuria and parasitaemia. There was no significant difference (p>0.05) in the creatinine levels of malaria patients and those without malaria. It is concluded that there is a form of renal impairment associated with malaria infection in Minna irrespective of age and sex.